Association between advanced oxidation protein products and 5-year mortality risk among amazon riparian elderly population. (February 2015) - Silva, T. O.; Jung, I. E. C.; Moresco, R. N.; Barbisan, F.; Ribeiro, E. E.; Ribeiro, E. A. M.; Motta, K.; Britto, E.; Tasch, E.; Bochi, G.; Duarte, M. M. F.; Oliveira, A. R.; et al.
Abstract Proteins are important targets of several modifications caused by oxidative stress, leading to structural changes and consequently partial or total loss of their functions. The oxidized proteins include advanced oxidation protein products (AOPP) derived from oxidation-modified albumin, as well as fibrinogen and lipoproteins. An increase in AOPP levels indicates an oxidative stress state and the presence of coexisting inflammation. Several investigations have also suggested an association between high AOPP levels and aging-related diseases. However, the link between elevated AOPP levels and elderly mortality risk has not yet been investigated. Here, we report on a 5-year longitudinal study that investigated the potential association between AOPP levels and mortality using a population-based representative sample of riparian elders living in Brazilian Amazon region (Maués-AM). Age, sex, socioeconomic and cultural conditions, chronic morbidities, polypharmacy, and previous morbidities were also tested as potential confounders. The AOPP levels were measured in 540 (84.78%) individuals, all of whom were followed over a 5-year period in order to establish the mortality rate. Within this study period, 74 (13.7%) elders died and 466 (86.3%) survived. The AOPP levels were higher among the elders who died within the 5-year period (46.27 ± 40.6 mmol/L) compared with those who survived (36.79 ± 20.84 mmol/L) (p = 0.002). The analysis confirmed the link between high AOPP levels and mortality risk, independent of other intervenient factors. These results suggest that elevated AOPP levels could be used to predict mortality risk in elderly patients.